The overview-analytical document of the international experience of building smart city - Bashynska, Iryna; Dyskina, Anastasia (Business: Theory and Practice, 2018)
The population of the planet is constantly growing, people are moving to the cities. Recently, more and more interest is being given to smart cities as a guarantee of at least comfortable living of citizens, as a maximum – an ultramodern autonomous city with artificial intellect, anticipating the needs of residents, capable of functioning autonomously for a long time. The purpose of the article is to analyze the experience of smart cities, highlight the distinctive and common features and outline the initial stages of the route map for the development of a specific city into a smart city. After the study, it became clear that the concept of “smart city” is very broad, scientists are investing a huge number of parameters that characterize a smart city, but it was possible to identify common characteristics. Also, the hypothesis was tested that the city’s urbanization should be oriented towards the inhabitants of this city, i.е. implemented not by a single algorithm, but by an algorithm that is adapted to the needs of a particular city. We proposed a methodology for the preparatory stage of the city’s self-mastering, which is based on expert assessments by a prior ranking, includes 2 stages and which was tested on the example of Odessa (Ukraine). At the first stage, the questionnaire contained questions about the six main characteristics of a smart city. At this stage three characteristics were singled out, which are of particular concern to Odessa citizens and the second survey contained 36 clarifying questions only for these three characteristics. The results allowed to distinguish 6 characteristics from which it is necessary to start Odessa’s growth as a smart city.